Identification of novel pyrazole and benzimidazole based derivatives as PBP2a inhibitors: Design, synthesis, and biological evaluation - Menna-Allah W. Shalaby; Eman M.E. Dokla; Rabah A. T. Serya; Khaled A. M. Abouzid (Ain Shams University, 2019)
The antibiotic resistance of methicillin-resistant Staphylococcus aureus (MRSA) is attributable to the expression of the high molecular mass transpeptidase enzyme, penicillin-binding protein 2a (PBP2a), an enzyme that catalyzes the cross-linking reaction step in the cell wall biosynthesis in the face of the challenge by β-lactam antibiotics. In the current study, ten pyrazole and benzimidazole based-compounds were designed, synthesized, and evaluated as anti-MRSA agents. These derivatives were screened for their antibacterial activity against two Staphylococcus (S.) aureus strains; methicillin-sensitive Staphylococcus aureus (MSSA) ATTC6538 and MRSA USA300 strains. Three of the tested compounds (XII, XIII, and XIV) exhibited moderate bactericidal activity against MSSA, MRSA, and vancomycin-resistant Staphylococcus aureus (VRSA) strains. Docking of these compounds into the allosteric site of PBP2a showed comparable binding modes to that of the lead quinazolinone PBP2a inhibitors suggesting a similar mode of action. The present study presents a promising candidate for further optimization as a potential PBP2a inhibitor targeting MRSA infection.